A method for improving the recovery of fluorescent aromatic compounds (FACs) from fish bile and a kit thereof - Varnamkhasti, Ali Karami (2011)
The present invention relates to a method and a kit for improving the recovery of fluorescent aromatic compounds (FACs) from fish bile. The method comprising: preparing a volume of bile sample from a fish; adding a volume of enzyme combination and a volume of distilled water to the volume of bile in order to obtain a mixture; incubating the mixture; adding a volume of acetone to the mixture; centrifuging the mixture and obtaining a supernatant and a pellet; and recovering the biliary FACs in the supernatant using high performance liquid chromatography with fluorescent detection (HPLC/FL). To increase accuracy of the method, pellets resulted from the centrifugation were resuspended in distilled water and the above-mentioned procedure was repeated but using different ratios of distilled water, enzyme combination, and acetone. The highly accurate result is required for accurate estimation of PAHs concentrations in aquatic environments. In addition, early estimation of low concentrations of PAHs in fish products through fish bile ensures the extra safe consumption of fish products by human and farm animals.